Anotasi Putusan Pengadilan Tata Usaha Negara Nomor: 124/G/LH/2016/PTUN-BDG - Muhammad Zeta Rifqi; Tiara Febiyola; Amelia Andriani; Adelia Puan Maharani; Zulfenia Arzilla Ramadhini; Cicilya Margareth Angelina (Hukum Inovatif : Jurnal Ilmu Hukum Sosial dan Humaniora, 2025)
The problem related to violation of RTRW is actually a common issue until now. Like the recent case, namely the fire that occurred at the Pertamina Plumpang Depot. The fire incident could actually be prevented by implementing proper spatial planning regulations. Based on the Regional Regulation (Perda) of DKI Jakarta Number 1 of 2012 concerning the 2030 Regional Spatial Planning, fuel oil (BBM) depots are required to have a buffer zone. Unfortunately, at the Pertamina Plumpang Depot, this buffer zone does not exist, so that residential areas are too close to the dangerous depot area. The purpose of this study is to find out the Annotation of the State Administrative Court Decision Number: 124 / G / LH / 2016 / PTUN-BDG. This research method uses a qualitative approach, with a special method applied, namely meta-analysis. Meta-analysis is a research technique used to combine findings from previous studies related to the same research topic. The results of the study show that among others Based on case information, it is known that there are 6 (six) plaintiffs who sued the Decree of the Head of the Investment and Integrated Licensing Agency of West Java Province Number: 660/10/19.1.02.0/BPMPT/2016 concerning the Environmental Permit for the Construction and Operational Activities of the 1x1000 MW Cirebon PLTU, Astanajapura District and Mundu District, Cirebon Regency by PT Cirebon Energi Prasarana. In its decision, the PTUN granted the lawsuit in its entirety.